ANALISIS KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH SEASONED EQUITY OFFERINGS (STUDI EMPIRIS PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2016) - Dwi Indarti Putri; Nur Hidayati; Abdul Wahid Mahsuni (Universitas Islam Malang, 2018)
ABSTRACTThe aim of this research is to analysis the differences between FinancialPerformance Factory before and after Seasoned Equity Offerings. The variable ofthis research are Debt to Equity Ratio, Return on Asset, Return on Equity,and NetProfit Margin. Sample of the research is Factory which did Seasoned EquityOfferings Marked as Right Issue on 2012-2016 during two years before SEO andtwo years after SEO. Based on the result using Paired Sample t-test was gottenthat there is significant differences between Debt to Equity Ratio and Net ProfitMargin factory which is include listing two years before and two years after SEO.While for Return on Equity and Return on Asset there is no significant differencebetween two years before and two years after SEO.Keyword: Financial Performance, ROA, ROE, NPM, DER, Right Issue